Healthcare in Ireland and Britain from 1850 : voluntary, regional and comparative perspectives - Lucey, Donnacha Seán; Crossman, Virginia (Institute of Historical Research, 2014)
" ... Explores developments in health and social care in Ireland and Britain during the nineteenth and twentieth centuries. The central objectives are to highlight the role of voluntarism in healthcare, to examine healthcare in local and regional contexts, and to provide comparative perspectives."--Back cover